2019
DOI: 10.4028/www.scientific.net/msf.944.1208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Volatile Organic Compounds (VOCs) during the Regeneration of Post-Consumed Poly(Ethylene Terephthalate) Using HS-GC-MS Method

Abstract: VOCs emissions from recycled PET are recognized as one of the major causes of poor healthy condition. Much attention has been increasingly focused on VOCs produced from regenerated PET for their significance in ecological safety. These emissions may be strongly influenced by the raw materials and manufacturing techniques of the recycled PET. However, there is very little published information regarding this issue. The purpose of this study was to examine VOCs releasing from reprocessed productions when exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Then, as on heating, the sample liberates volatile organic compounds (VOCs). This technique measures the heating time for produced VOCs, identifies them, and quantifies the compounds produced (Liu et al 2018b). Dümichen et al (2017) used thermal extraction desorption gas chromatography-mass spectroscopy to determine the quantity of organic and inorganic components in the soil matrix, such as ethyl benzoate and vinyl benzoate.…”
Section: Thermal Extraction Desorption Gas Chromatography-mass Spectr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Then, as on heating, the sample liberates volatile organic compounds (VOCs). This technique measures the heating time for produced VOCs, identifies them, and quantifies the compounds produced (Liu et al 2018b). Dümichen et al (2017) used thermal extraction desorption gas chromatography-mass spectroscopy to determine the quantity of organic and inorganic components in the soil matrix, such as ethyl benzoate and vinyl benzoate.…”
Section: Thermal Extraction Desorption Gas Chromatography-mass Spectr...mentioning
confidence: 99%
“…Divinyl terephthalate, mono-vinyl terephthalate, benzene, toluene and terephthalic acid were the primarily identified products at 435 °C temperature pyrolysis using thermogravimetric analysis-mass spectroscopy analysis (Hujuri et al 2013). It is further explored by Liu et al (2018b) to detect the volatile organic compounds composition during the thermal degradation of PET fibres and popcorn. It was observed that the methylbenzene, styrene, formaldehyde, acetaldehyde and benzaldehyde compounds were present (Liu et al 2018b).…”
Section: Thermogravimetric Analysis-mass Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…After the washing unit, the polymer is melted utilizing screw extruders. The extrusion unit plays an essential role in the formation of VOC emissions from plastic, as the plastic is melted at high temperatures through the rotating screw, thus facilitating the degradation of the material and the release of breakdown products (S. S. Liu et al, 2019).…”
Section: Washing Linementioning
confidence: 99%
“…The main drawbacks of reprocessing recycled post-consumer plastic waste is the advanced stage of degradation of the polymer as well as the levels of contaminants in the recycled material . Most of the contaminants present in post-consumer plastic waste are related to organic compounds, including volatile organic compounds (VOCs), some of which have been reported to be of particular concern for human health, such as benzene that was detected in post -consumer recycled PET, as reported by Liu et al (2019). In addition, substances causing unwanted smells have been identified in post-consumer plastics whose origin is related to their previous use phase .…”
Section: Introductionmentioning
confidence: 99%